Legal Protection of Minors Who Did the Dissemination of Immoral Videos on Social Media - Nila Indrika Anggi Finanda (International Forum of Researchers and Lecturers, 2022)
Legal protection of children refers to all actions that ensure and safeguard children and their rights so that they can live, grow, develop, and engage maximally in line with human dignity and honour, as well as get protection from violence and discrimination within legal laws. In Indonesia, the proportion ranges from 22 to 100%, indicating that the aforementioned conditions occur often. As a result, researchers are interested in performing this study utilising normative research methodologies. Legal protection for minors who distribute pornographic videos on social media, choosing to release minors, is regulated by Law No. 23 of 2002 concerning Child Protection, Article 16 (1) Every child has the right to receive protection from being the target of abuse, torture, or inhumane punishment, (2) Every child has the right to obtain freedom in accordance with the law, and (3) Arrest, detention, or incarceration of a child must be carried out in accordance with relevant legislation and only as a last option. And advocate LPKA in the form of independence coaching, which includes instruction for foster children in skills that may be developed after the foster time ends, such as sewing. Meanwhile, personality development is moral development, with the goal of providing foster children with an understanding of social norms as well as an understanding of themselves so that they can accept responsibility for all actions they take and refrain from repeating illegal actions. Suggestions in this protection are expected to be safeguarded by anybody, regardless of circumstance, and the local government needs to get to the field to inspect the status of special child development institutions so that any deficiencies may be corrected quickly, allowing development to proceed correctly.